PENGARUH TENURE KAP, UKURAN KAP, SPESIALISASI AUDITOR DAN AUDIT FEE TERHADAP KUALITAS AUDIT DENGAN MODERASI KOMITE AUDIT - Anastasia Angesti Nurintiati; Agus Purwanto (Diponegoro Journal of Accounting, 2017)
There are still debate whether long audit tenure will decrease auditor’s independency which effecting the quality of audit. This research has an objective to analyze the relation and effect between audit tenure, accounting firms specialization, accounting firms size and audit fee to audit quality moderated by audit committee.By using a data collected from Annual Report manufacture companies listed in Indonesia Stock Exchange (IDX) periode 2013 – 2015 and attached information about audit fee. This research use linier regression and Moderated Regression Analysis (MRA) along with purpossive sampling method, 154 companies were obtained.Result from this research shown that tenur and audit fee have a significant effect to audit quality which proxied with discreationary accrual. While accounting firms size and auditor spesialization have no significance to audit quality. The role of audit committee was able to modarate between tenur and audit quality.